La crítica como anécdota y un futuro para el periodismo. (A propósito del caso Echevarría) - Rivas Troitiño, José Manuel (Estudios sobre el Mensaje Periodístico, 2005)
A “disparaging” critique in a newspaper’s literary supplement, of a book brought out by a publisher belonging to the same publishing group as the daily in question, offers an occasion to reflect on the present state of journalism. It is not the book’s author who turns against the critic, but rather the critic who turns against the medium in which he is published and the medium against the critic. Using this anecdote as a weathervane, an optimistic view can be taken of journalism’s crisis: internet is serving and can serve as a setting for journalistic credibility, independence and professionalism.
Keywords: journalism; criticism; credibility; internet